Cloning and expression analysis of three genes encoding ubiquitins in papaya (Carica papaya L.). Issue 2 (3rd March 2016) - Geng, J. J.; Shen, Y. H.; Yang, F. Y.; Li, K.; Chen, X. J.
ABSTRACT: Papaya ( Carica papaya L.) fruit have a short shelf-life due to rapid ripening induced by ethylene, which usually results in a high percentage of product loss. However, little is known about the genetic mechanism of ripening and the attributes of fruit quality. Ubiquitin (UBQ) proteins have received increasing attention because they play important roles in response to ripening and in regulating certain developmental processes in plants. In the present study, three genes encoding UBQ proteins, CpUBI1, CpUBI2, and CpUBI3, were isolated from papaya fruit. The lengths of the cDNAs of CpUBI1, CpUBI2, and CpUBI3 were 1, 485 bp, 1, 642 bp, and 529 bp, encoding 306, 308, and 156 predicted amino acids, respectively. Sequence analysis demonstrated that the CpUBI1 and CpUBI2 proteins contained four consecutive structural domains of the UBQ superfamily, while CpUBI3 contained a ribosomal domain structure of the S27a superfamily. RT-qPCR analysis demonstrated that ethephon treatment increased CpUBI gene expression significantly, compared to 1-methylcyclopropene (1-MCP) treatment and the untreated controls. Levels of CpUBI1 and CpUBI2 gene expression were significantly higher than CpUBI3 . These results suggested that CpUBI1, CpUBI2, and CpUBI3 might have different roles during papaya fruit ripening and softening.